Singapore Airlines : service recovery and customer repurchase decisions (a case study). - Shanmugam, Jayaraj. (2008)
This is a study of the correlation between service recovery and customer repurchase decisions. Customers who experienced service failures and who experienced service recovery are more positive about the firm than those who do not. Such customers will continue to repurchase as long as they feel that the firm has resolved their problems in a satisfactory manner. Singapore Airlines (SIA), world renowned for its service quality, has comprehensive service recovery procedures in place, to ensure that if it did not get the service right the first time, it will spare no effort in doing it better the second time around. Such comprehensive procedures ensure that customers who experience service failures do not go away disappointed, wishing that they never used the airline in the first place. Instead, they are overwhelmed by the service recovery provided that that they are more positive about the airline and continue to fly with them.